Penerapan Pembangunan yang Partisipatif di Distrik Holuwon Kabupaten Yahukimo - Kobak, Sem; Veplun, Dirk; Saleh, Kasim (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This study aims to see how far the level of village community participation in development programs is being promoted at the Holuwon District level, Yahukimo Regency. Then describe the supporting and inhibiting factors of community participation in the development program. The research method used is descriptive qualitative. The choice of research location was in the Holuwon District, Yahukimo Regency, with consideration of accessibility in conducting research. Data collection techniques used are interviews and observation as well as documentation. Data analysis includes the stages of data reduction, data presentation, and data verification as well as the conclusion. The results of the study show that the people who participate in the implementation of development mostly want change and regional progress so they actively participate in preparing development plans until the implementation of development is complete. This is because the community is active in discussing development planning, then the community is also involved in providing interactive information. Supporting factors are support from the Government, coordination between agencies, and the will of the community in progressing development. Inhibiting factors are internal factors which include limited knowledge and insight into the community, lack of community will, and external factors which include geographical conditions and low geographic quantity of employees.Â Â